Awareness of Dysphagia-Related Complications and Risks and the Importance of Early Intervention in Patients with Parkinson’s Disease: A Qualitative Study - Kaifeng Yao; Lihua Wang; Lihua Zhang (International Journal of Clinical Practice)
Objective. To investigate the awareness of dysphagia-related complications and risks and the importance of early intervention in patients with Parkinson’s disease (PD). Methods. Using the phenomenological approach of the qualitative study, 18 patients with PD in a Grade A tertiary hospital in Nantong were selected, and semistructured personal in-depth interviews were conducted. The interview content was analyzed using Colaizzi’s seven-step method, and the topics and subtopics were further refined. Results. Awareness of dysphagia-related complications and risks and the importance of early intervention in patients with PD can be summarized into three topics: lack of knowledge about PD and dysphagia, changes in emotional cognition, and low need for early intervention for dysphagia. Conclusions. Patients with PD have a low awareness of dysphagia, do not follow any preventative measures, and have difficulty in recognizing the disease symptoms; hence, there is a vital need for early intervention. Medical staff need to create awareness among patients and their families, provide health education through multiple channels, popularize the knowledge of PD complications such as dysphagia, improve patient compliance with respect to medication, regular consultation, and medical treatment, guide the transformation of negative emotions in patients to positive emotions, and help patients with PD to actively prevent dysphagia and other complications and improve their quality of life.